The residential reality of displaced families to the city of LatakiaA field research in the Saqubin area (Damascus University Journal of arts and humanities sciences, 2025)
The research aimed to monitor the housing reality of displaced families to the city of Latakia by identifying the reasons for the suffering of displaced families in finding housing, and identifying the reasons that push displaced families to choose specific residential areas, and identifying the reasons that push displaced families to change their area of ​​residence. The research relied on the descriptive analytical method, and used the sample social survey method, and the questionnaire as a tool for collecting data. It included a study of a sample of (300) families displaced to the city of Latakia, out of (7354) families located in the Saqubin area, and the unit of analysis was only the father or mother from the family. The research showed that the majority ofdisplaced families in the city of Latakia live in rented housing, with a percentage of (69.66%) of the sample members. The displaced families suffered from difficulty in finding housing, with a high percentage of (83.66%) of the sample members. The most prominent reason for this difficulty was the high rental prices. by (45.41%) of the sample members who faced difficulty. The displaced families also chose specific residential areas with a very high percentage of (87%) of the sample members, and the most prominent reason for their choice was the presence of relatives or acquaintances by (49.80%) of the sample members who They lived in specific areas, and displaced families changed their area of residence at a high rate of (79.33%) of the sample members. The most prominent reason for changing the area of residence was the instability of rental prices at a rate of (47.47%) of the sample members who changed their area of residence.
Keywords: Housing; , Family; , Displacement